PENGEMBANGAN MEDIA KOMIK BERGAMBAR PADA TEMA 6 ENERGI DAN PERUBAHANNYA DI KELAS III SD NEGERI 117863 RIMBAYA - Febby Awliyah Nasution; Lala Jelita Ananda (Universitas Negeri Medan, 2020)
Abstract: The problem in this research is the lack of thematic learning media and the never developed pictorial comic media on the theme of energy and its changes in grade III SD Negeri 117863 Rimbaya. The purpose of this study was to produce pictorial comic media on the theme of 6 Energy and Its Change which was appropriate for grade III students of SD Negeri 117863 Rimbaya. This study used a Research and Development (R&D) design. The research instrument consisted of observation, the third grade teacher's interview sheet at SD Negeri 117863 Rimbaya and the expert validation questionnaire. The pictorial comic media was developed referring to the Borg and Gall development stage with 5 stages, namely: potential problems, data collection, product design and production of pictorial comic media, expert validation and product revision. The results showed that the evaluation of the material and media experts at stage I by the validator got an average score of 3.75 in good categories. While the validation of media experts in stage I by the validator got an average score of 3.85 in the good category. If the figure is converted into a Likert scale based on the feasibility level, then the pictorial comic media is in the feasible category with revision. After making improvements to the material and media in stage I, the validator's evaluation of material experts in stage II was obtained with an average score of 4.33 in the very good category. In the validation of media experts in stage II by the validator, it got an average score of 4.35 which was categorized as very good and feasible without revision. Based on the explanation above, it can be concluded that the pictorial comic media on Theme 6 Energy and Change is suitable for learning for Class III students of SD Negeri 117863 Rimbaya, NA IX-X District, Labuhan Batu Utara Regency T.A 2020/2021.Keywords: Comic Pictures, Theme 6 Energy and Change, Class III Elementary School.Abstrak: Masalah dalam penelitian ini adalah minimnya media pembelajaran tematik serta belum pernah dikembangkannya media komik bergambar pada tema energi dan perubahannya di kelas III SD Negeri 117863 Rimbaya. Tujuan Penelitian ini adalah menghasilkan media komik bergambar pada tema 6 Energi dan Perubahannya yang layak untuk siswa kelas III SD Negeri 117863 Rimbaya. Penelitian ini menggunakan desain Research and Development (R&D). Instrumen penelitian ini terdiri dari observasi, lembar wawancara guru kelas III SD Negeri 117863 Rimbaya dan Angket/Kuesioner validasi ahli. Media komik bergambar dikembangkan mengacu pada tahap pengembangan Borg and Gall dengan 5 tahap yaitu : potensi masalah, pengumpulan data, desain produk dan produksi media komik bergambar, validasi ahli dan revisi produk. Hasil penelitian menunjukkan bahwa penilaian dari ahli materi dan media pada tahap I oleh validator mendapatkan rata-rata skor 3,75 kategori baik. Sedangkan validasi ahli media pada tahap I oleh validator mendapatkan rata-rata skor 3,85 kategori baik. Apabila angka tersebut dikonversikan ke dalam skala Likert berdasarkan tingkat kelayakan, maka media komik bergambar